THU0099 The 2010 classification criteria and a more aggressive treatment strategy improve clinical outcomes in seropositive but not seronegative rheumatoid arthritis. (15th June 2017) - Crepaldi, G; Bugatti, S; Benaglio, F; Sakellariou, G; Manzo, A; Montecucco, C; Caporali, R
Abstract : Background: Current guidelines recommend an early and intensive treatment in patients diagnosed with rheumatoid arthritis (RA), and the 2010 ACR/EULAR Classification Criteria were developed with the aim of allowing earlier diagnosis and treatment (1, 2). Recent studies highlighted some differences in disease activity between seropositive and seronegative RA patients at disease onset (3). Objectives: To investigate whether the application of the 2010 ACR/EULAR Classification Criteria and a more aggressive treatment strategy improve clinical outcomes in patients with early RA irrespective of the autoantibody status. Methods: 584 early, treatment-naïve RA patients were recruited in the years 2005–2014. RA diagnosis was made according to the ACR 1987 criteria in 2005–2010 (n=360, cohort 1987), and to the 2010 ACR/EULAR criteria in 2011–2014 (n=224, cohort 2010). Patients were classified in autoantibody (Ab)-negative (negative rheumatoid factor (RF) and/or anticitrullinated peptide antibody (ACPA) and Ab-positive (RF and/or ACPA positive). Methotrexate (MTX) was used at the initial dosage of 10 mg/week in cohort 1987, and 15 mg/week in cohort 2010, and progressively increased if low disease activity (LDA) (DAS28≤3.2) was not met. The frequency and predictors of LDA and clinical remission (DAS28<2.6) over 6 months were assessed by Cox regression. Results: In Ab-negative patients, LDA and clinical remission were achieved in 62.8% and 37.2% of the cases, and the 2010 cohort did not show significantly improved outcomes (HR [95% CI] 0.86 [0.611.23] for LDA; 1.04 [0.651.69] for remission) (Figure 1 A, B). In contrast, in Ab-positive patients, the application of the 2010 classification criteria and higher dosages of MTX were associated with increased frequency of LDA after adjustment for confounders (age, sex, prednisone, baseline DAS28; HR [95% CI] 1.39 [1.012]) (Figure 1 C). Clinical remission was achieved in 41.3% of the cases, compared to 29.6% in the 1987 cohort (p=0.17) (Figure 1 D). Conclusions: Early diagnosis and a more aggressive treatment strategy with MTX lead to significantly improved outcomes in autoantibody positive RA. The management of seronegative patients remains suboptimal. References: Smolen JS et al. Treating rheumatoid arthritis to target: 2014 update of the recommendations of an international task force. Ann Rheum Dis 2016. Aletaha D et al. 2010 rheumatoid arthritis classification criteria: an ACR/EULAR collaborative initiative. Ann Rheum Dis 2010. Nordberg LB et al. Patients with seronegative RA have more inflammatory activity compared with patients with seropositive RA in an inception cohort of DMARD naive patients classified according to 2010 ACR/EULAR criteria. Ann Rheum Dis 2017. Disclosure of Interest: None declared